PEMETAAN PILIHAN LULUSAN SMK PANCA BUDI MEDAN MENGGUNAKAN ALGORITMA K-MEANS DAN VISUALISASI DATA - Maida Indrayani; Muhammad Iqbal; Darmeli Nasution (Smart Education, 2025)
Abstract: This research maps the career choices of SMK Panca Budi Medan graduates using the K-Means algorithm and data visualization. The study included 219 graduates from 2024 across eight study programs. The majority (44.7%) chose to work, followed by 32.0% who pursued higher education, 16.4% were undecided, and 6.8% became entrepreneurs. Graduates with higher average report card scores tended to continue their studies, while those with lower scores often opted to work or were undecided. The K-Means algorithm successfully clustered graduates, with Cluster 1.0 showing the highest academic potential (average score: 94.60). The findings provide strategic recommendations for the school, including intensifying career guidance for undecided graduates, strengthening higher education pathways for high-achievers, accelerating entrepreneurship incubators, and implementing personalized alumni coaching based on clustering analysis.Â Keywords: Tracer Study, K-Means, Data Visualization, SMK, Alumni Outcomes Abstrak: Penelitian ini memetakan pilihan karier lulusan SMK Panca Budi Medan menggunakan algoritma K-Means dan visualisasi data. Studi melibatkan 219 lulusan tahun 2024 dari delapan program studi. Sebagian besar lulusan (44,7%) memilih langsung bekerja, diikuti oleh 32,0% yang melanjutkan kuliah, 16,4%